2017
DOI: 10.1249/mss.0000000000001380
|View full text |Cite
|
Sign up to set email alerts
|

Hockey Fans in Training

Abstract: IntroductionHockey Fans in Training (Hockey FIT) is a gender-sensitized weight loss and healthy lifestyle program. We investigated 1) feasibility of recruiting and retaining overweight and obese men into a pilot pragmatic randomized controlled trial and 2) potential for Hockey FIT to lead to weight loss and improvements in other outcomes at 12 wk and 12 months.MethodsMale fans of two ice hockey teams (35–65 yr; body mass index ≥28 kg·m−2) located in Ontario (Canada) were randomized to intervention (Hockey FIT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 40 publications
3
70
0
1
Order By: Relevance
“…In 2014, a research team based at London University, Ontario obtained funding from the Men's Health Charity, Movember, to undertake a pilot pragmatic RCT of FFIT delivered in Canadian ice hockey clubs. The Hockey FIT initiative reflects the popularity of ice hockey in Canada; two-thirds of adult Canadians are said to follow ice hockey as a fan, and 80% identify it as "a key part of what it means to be Canadian" [55] (p. 2507). Hockey FIT is adapted directly from FFIT [56] (p. 3) and uses the "love of [ice] hockey", rather than football (soccer), as the hook.…”
Section: Hockey Fit-deliveries To Men Through Canadian Ice Hockey Clubsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, a research team based at London University, Ontario obtained funding from the Men's Health Charity, Movember, to undertake a pilot pragmatic RCT of FFIT delivered in Canadian ice hockey clubs. The Hockey FIT initiative reflects the popularity of ice hockey in Canada; two-thirds of adult Canadians are said to follow ice hockey as a fan, and 80% identify it as "a key part of what it means to be Canadian" [55] (p. 2507). Hockey FIT is adapted directly from FFIT [56] (p. 3) and uses the "love of [ice] hockey", rather than football (soccer), as the hook.…”
Section: Hockey Fit-deliveries To Men Through Canadian Ice Hockey Clubsmentioning
confidence: 99%
“…Components from HealtheSteps TM were also included (e.g., "lifestyle prescriptions", and access to a private online social network platform and HealtheSteps TM smartphone app). Participants were encouraged to engage with these tools post-program during a "forty-week minimally supported phase" (see [55]). However, process evaluation data from the pilot RCT showed that the HealtheSteps TM smartphone app "was not used by participants due to technical challenges experienced by the men (i.e., difficulties signing in, not tracking steps, crashing)" and analysis of interviews with participants 12 months after baseline measures showed that "the Hockey FIT social network was used passively with men only accessing the HeatheSteps TM network when they received a message/post from their coach or another participant.…”
Section: Hockey Fit-deliveries To Men Through Canadian Ice Hockey Clubsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFIT concept has spread across the world via rugby (RUFIT-NZ, New Zealand) [20], football (Aussie-FIT, Australia) [21] hockey (Hockey FIT, Canada) [18] [19] and in Europe via EuroFIT [23]. Thus, this type of intervention needs refinement to fit into different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…FFIT has also inspired other sports. Within the Canadian context, Hockey Fans in Training (Hockey FIT) has developed with promising results [18] [19].…”
Section: Introductionmentioning
confidence: 99%